2016
DOI: 10.1177/0022034515624443
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Performance Analysis of a Novel Bone Level Tapered Implant

Abstract: Primary mechanical stability, as measured by maximum insertion torque and resonance frequency analysis, is generally considered to be positively associated with successful secondary stability and implant success. Primary implant stability can be affected by several factors, including the quality and quantity of available bone, the implant design, and the surgical procedure. The use of a tapered implant design, for instance, has been shown to result in good primary stability even in clinical scenarios where pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
1
21
1
Order By: Relevance
“…Mean insertion torque of Ti‐Unite Branemark III implants placed in the posterior maxilla was 22 Ncm in type III bone and 17 Ncm in type IV bone (Alsaadi, Quirynen, Komárek, & Steenberghe, ); other studies in the posterior maxilla also reported low mean insertion torques between 10 and 30 Ncm (Alsaadi et al, ; Beer, Gahleitner, Holm, Tschabitscher, & Homolka, ). It is accepted that the insertion torque of tapered implants is superior to paralleled‐wall implants (Dard et al, ; Javed et al, ). Comparing these data seems to confirm that implant design plays a critical role when a threshold insertion torque is aimed at a demanding bony environment.…”
Section: Discussionmentioning
confidence: 99%
“…Mean insertion torque of Ti‐Unite Branemark III implants placed in the posterior maxilla was 22 Ncm in type III bone and 17 Ncm in type IV bone (Alsaadi, Quirynen, Komárek, & Steenberghe, ); other studies in the posterior maxilla also reported low mean insertion torques between 10 and 30 Ncm (Alsaadi et al, ; Beer, Gahleitner, Holm, Tschabitscher, & Homolka, ). It is accepted that the insertion torque of tapered implants is superior to paralleled‐wall implants (Dard et al, ; Javed et al, ). Comparing these data seems to confirm that implant design plays a critical role when a threshold insertion torque is aimed at a demanding bony environment.…”
Section: Discussionmentioning
confidence: 99%
“…In low-density bone sites, the dental implant macrodesign needs to guarantee an acceptable primary stability 2,6,10,[22][23][24]30 ; and stability tends to increase with length and width, so long and wide implants are still preferable. However, their installation requires sufficient thickness of the alveolar crest.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, clinical data related to the healing process such as implant stability quotient (ISQ) values and peri‐implant health are not present in literature. In addition, in vitro studies comparing the performance of tapered and cylindrical implants yielded variable and inconsistent results …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth publication, by Dard et al (2016), defends the concept of integrative performance analysis applied to a novel bone-level tapered implant. They propose successively conducting bone type-specific drill procedures that ensure maximum insertion torque values within the range of 15 to 80 N•cm when measured by maximum insertion torque and resonance frequency analysis.…”
Section: Introductionmentioning
confidence: 99%